Post Covid-19 Pandemic: Non-Accounting Undergraduate Students’ Resilience Towards Accounting Course Learning - Nur Diyana Ismail; Che Siti Lazrina Md Lazim; Mohd Danial Afiq Khamar Tazilah (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
This study is a conceptual paper to further explore various factors that increase the resilience of non-accounting undergraduate students to learn accounting course in the post Covid-19 pandemic. This study is concerned with academic issues such as poor motivation and concentration problems faced by non-accounting undergraduate students. Therefore, this study will discuss the application of Resilience Theory to observe how non-accounting undergraduate students enhance resilience to assist them understand accounting principles. This paper would raise important concern about the personal struggle of non-accounting undergraduate students in taking accounting course in the future.